Computer-simulated experiments and computer games: a method of design analysis - Jerome J. Leary (Association for Learning Technology, 1995)
Through the new modularization of the undergraduate science degree at the University of Brighton, larger numbers of students are choosing to take some science modules which include an amount of laboratory practical work. Indeed, within energy studies, the fuels and combustion module, for which the computer simulations were written, has seen a fourfold increase in student numbers from twelve to around fifty. Fitting out additional laboratories with new equipment to accommodate this increase presented problems: the laboratory space did not exist; fitting out the laboratories with new equipment would involve a relatively large capital spend per student for equipment that would be used infrequently; and, because some of the experiments use inflammable liquids and gases, additional staff would be needed for laboratory supervision.